A randomised controlled trial on the effect of inhaled hypertonic saline on quality of life in primary ciliary dyskinesia. Issue 2 (23rd February 2017) - Paff, Tamara; Daniels, Johannes M.A.; Weersink, Els J.; Lutter, René; Vonk Noordegraaf, Anton; Haarman, Eric G.
Hypertonic saline inhalation lowers airway mucous viscosity. Increased cough transportability may improve quality of life (QoL) in primary ciliary dyskinesia (PCD). In this randomised controlled trial (RCT), PCD patients received twice-daily inhalations of hypertonic (7%) saline or isotonic (0.9%) saline for 12 weeks, with 4 weeks washout during crossover. Primary outcome was change in QoL measured by the St George's Respiratory Questionnaire (SGRQ) total score. Secondary outcomes were SGRQ subscores, Quality of Life Questionnaire-Bronchiectasis (QoL-B) scores, lower respiratory tract infection symptoms, exacerbations, spirometry, systemic and sputum inflammatory markers, adherence, and adverse events. There was no significant change in median (interquartile range) SGRQ total score between hypertonic saline (−2.6 (−9.0–1.5)) and isotonic saline (−0.3 (−8.1–6.1)) in 22 patients (age range 22–73 years) (p=0.38). QoL-B Health Perception scale improved with hypertonic saline (p=0.03). Adverse events occurred more frequently with hypertonic saline, but were mild. 12 weeks of inhaled hypertonic saline did not improve SGRQ total score in adult PCD patients in this RCT, but the sample size was small. On the secondary and more disease-specific end-point of the QoL-B, a significant improvement was observed in the Health Perception scale. This study found little evidence to support the hypothesis that hypertonic saline improves QoL in PCD patients. We advise the use of disease-specific outcome measures in future trials. RCT in PCD: hypertonic saline does not improve SGRQ scores, but improves health perception http://ow.ly/uL6x306Dmzh